2019
DOI: 10.1109/jphot.2019.2912156
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Indoor Visible Light Positioning Using Deep Neural Network Based on the Bayesian Regularization With Sparse Training Point

Abstract: In this letter, we propose an indoor visible light positioning technique that combines deep neural network based on the Bayesian Regularization (BR-DNN) with sparse diagonal training data set. Unlike other neural networks, which require a large number of training data points to locate accurately, we realize the high precision positioning with only 20 training points in a 1.8 m × 1.8 m × 2.1 m location area. Furthermore, we test a new optimization method of training data set, which is the diagonal set. To verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…This is where data-driven approaches can offer advantages. One of these models, used in the context of VLP, is the MLP model [21,22], of which the structure is shown in Figure 1. An MLP consists of at least three layers: an input layer (represented by vector z 0 ) containing the features (relative intensities), one or more hidden layers (represented by vector z i ), and an output layer (represented by vector z o ) (predicting the position).…”
Section: Multilayer Perceptronmentioning
confidence: 99%
See 1 more Smart Citation
“…This is where data-driven approaches can offer advantages. One of these models, used in the context of VLP, is the MLP model [21,22], of which the structure is shown in Figure 1. An MLP consists of at least three layers: an input layer (represented by vector z 0 ) containing the features (relative intensities), one or more hidden layers (represented by vector z i ), and an output layer (represented by vector z o ) (predicting the position).…”
Section: Multilayer Perceptronmentioning
confidence: 99%
“…The classical VLP schemes have limitations, as often they require close to ideal behavior of the propagation model and its parameters to perform well. Recently, however, it was demonstrated that Machine Learning (ML) techniques like for example Artificial Neural Networks (ANNs) are capable of delivering accurate localization results in the context of VLP [21][22][23][24][25], as they can handle noise naturally and are not bounded by ideal physical behavior. Furthermore, linear interpolation techniques can be used to reduce the amount of required measured data [26].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect method could be also characterized in different types of parameters that are applied in localization such as TDOA [31]- [34], FDOA [32] and AOA [33]. Except for distance or angle based positioning methods mentioned above, there are feature based or neural network based indoor positioning methods [35]- [37]. Usually, in neural network based method, measurements of RSSI (Received Signal Strength Indicator) are used to establish a database and then the database can be applied for the learning of neural network to locate the target.…”
Section: Introductionmentioning
confidence: 99%
“…Through an in-depth analysis in this subsection, it was confirmed that most of the results were affected by the LED placement. Meanwhile, some nodes (10,15,20,24), which were judged to have a relatively insignificant impact, showed much better performance than other nodes. This indicates that although the results of this experiment are excellent, if the structure of the transmitter is supplemented with a completely symmetrical LED arrangement or a single LED that is capable of controlling the intensity is used, better results can be obtained.…”
Section: Discussion Of Error Tendencymentioning
confidence: 99%
“…For example, in [17], [18], high accuracy three-dimensional positioning was studied by applying an artificial neural network (ANN), but due to a long operation time and a large amount of computation, these methods are difficult to apply to industry. In [19], [20], the speed of ANN was improved by efficiently reducing the data or optimizing the structure, however, the burden of collecting training data and adjusting detailed parameters, which is a problem of pre-learning-based machine learning, is still required. In [21], Cai et al proposed the positioning system based on modified particle swarm optimization (PSO) algorithm that shows high localization accuracy and significantly lower algorithm complexity.…”
Section: Introductionmentioning
confidence: 99%